Studying the state through the lens of Bolsa Família: policy preservation under adverse circumstances in Brazil - Bolch, K (2022)
In the 1990s and early 2000s, countries across Latin America embarked on a new era of social policy. Turning away from a model of “truncated” welfare states where social protection was tied to formal employment, governments began to expand the reach of social safety nets to new groups. Conditional cash transfers programs (CCTs) targeted to low-income households were a hallmark of this new approach and have since proliferated rapidly across the region and the world. In many countries, CCTs represented the first time that certain marginalized groups were direct beneficiaries of programmatic state-led social protection efforts. In this context, cash transfer programs represented not only a technical policy solution for poverty reduction, but also sought to push towards a deeper reimagining of state’s relationship with poor citizens. However, several decades on, the institutional environment in Latin America has changed dramatically. In recent years, it has been shaped by rising right-wing countermovements, shifting economic winds, and overlapping global crises. While there is an extensive body of research studying cash transfer programs during the earlier period of welfare state expansion, more contemporary research is needed to understand the political economy of how these policies have evolved in the face of adverse circumstances and to unpack their implications for the dynamic and contingent relationship between states and their citizens.